Optimization of an Incubation Step to Maximize Sulforaphane Content in Pre-Processed Broccoli - Mahn-Osses, A (Springer India, 2016)
Sulforaphane is a powerful anticancer compound, found naturally in food, which comes from the hydrolysis of glucoraphanin, the main glucosinolate of broccoli. The aim of this work was to maximize sulforaphane content in broccoli by designing an incubation step after subjecting broccoli pieces to an optimized blanching step. Incubation was optimized through a Box–Behnken design using ascorbic acid concentration, incubation temperature and incubation time as factors. The optimal incubation conditions were 38 °C for 3 h and 0.22 mg ascorbic acid per g fresh broccoli. The maximum sulforaphane concentration predicted by the model was 8.0 µmol g−1, which was confirmed experimentally yielding a value of 8.1 ± 0.3 µmol g−1. This represents a 585% increase with respect to fresh broccoli and a 119% increase in relation to blanched broccoli, equivalent to a conversion of 94% of glucoraphanin. The process proposed here allows maximizing sulforaphane content, thus avoiding artificial chemical synthesis. The compound could probably be isolated from broccoli, and may find application as nutraceutical or functional ingredient. © 2016, Association of Food Scientists & Technologists (India).